Debt, Gross Domestic Product and money in St. Kitts and Nevis 1983-1998 - Jones-Hendrickson, S. B. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1999)
Assesses public debt, GDP and money in St. Kitts and Nevis over the period 1983 to 1998. Seeks to determine whether any salient conclusions can be drawn about debt, GDP and money over that period in light of Domar Macro Debt models.